Specific Diagnosis of Brain Disease with Double Isotope Brain Scanning - EII, P. J.; Lotritsch, K. H.; Hilbrand, E.; Meixner, M.; Barolin, G.; Scholz, H. (Nuklearmedizin - NuclearMedicine, 1976)
25 patients with known cerebral disease (either CVA’s or primary or secondary tumours) diagnosed by clinical and angiographic criteria were submitted to a double siotope imaging technique using 99mTcO4– and 99mTc-EHDP.The different biological behaviour of these radiopharmaceuticals has provided specific and differential diagnosis between vascular and neoplastic disease of the brain. 99mTc-EHDP is shown to be the tracer of choice for the imaging of CVA’s and 99mTcO4– is confirmed as the tracer of choice for the imaging of primary or secondary tumours in the brain.